Enhanced mechanical, thermal and optical properties of poly (vinyl alcohol)/functionalized-graphitic carbon nitride composites - Tari, Esra; Ugraskan, Volkan; Yazici, Ozlem (TAYLOR & FRANCIS INC, 2024)
Poly (vinyl alcohol) (PVA) composite films containing oxidized graphitic carbon nitride (GCN-ox) were successfully prepared by solution casting. First, GCN was synthesized and delaminated, and then its surface was oxidized. Composites containing 0.5%, 1%, 2%, 3%, 4%, and 5% by mass of GCN-ox were prepared. Composites were characterized by XRD, SEM, FTIR-ATR, and UV-vis analyses. In addition, tensile strength and elongation at break values of composite samples were determined by mechanical tests. Because of the increasing interfacial interaction between GCN-ox and the PVA matrix, GCN-ox acted as a reinforcing filler to enhance the mechanical properties. PVA/GCN-ox composites could reach 52.5 MPa tensile strength and 7.27 GPa tensile modulus, respectively. Optical studies showed that the energy bandwidth of the pristine PVA reduced from 4.983 eV to 3.813 eV with the addition of 5% GCN-ox.
Keywords: Poly (vinyl alcohol); graphitic carbon nitride; mechanical; thermal; optical properties; Chemistry; Science & Technology - Other Topics; Materials Science; Physics